IMPLEMENTASI REHABILITASI SOSIAL BAGI PENYANDANG DISABILITAS DI KOTA PEKANBARU - Vawitrie, Yulia; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Social Rehabilitation is a refunctionalization and development for people with social problems to allow them for doing their social function reasonably in daily life. Person with disabilities is a person that has limitation on physical, intellectual, mental, and sensory in long-term period and have an obstacle when interact in the circle. Based on observation in the field, problem that occur in the implementation on social rehabilitation for person with disabilities is most of the families of persons with disabilities have economic condition on middle to lower class, so they don’t have an education, which make them role in working is low and they got exiled from society. The purpose of this research is to analyze the implementation of social rehabilitation for person with disabilities di Pekanbaru City and factor that affect the implementation. The Theory concept used is Implementing Policy Theory by Edward III. This research also used qualitative research methods by analyzing the data descriptively. Source data that used is primary and secondary, with data collection techniques : interviews, observations, documentation. Result of this research shows that the implementation of social rehabilitation for person with disability is not effectively, this is proven by still many of these persons of disabilities not yet get social rehabilitation from government. The factors that affect the implementation is there are resource that not enough and lack of awareness of society to contribute in the process of implementation of social rehabilitation for persons with disabilities.Keyword : Social Rehabilitation, Implementation, Persons with Disabillities, Social Welfare